John Burnham orderly - Burnham, John.
Volume of orders (1777 January 28-December) for Gen. Benjamin Lincoln kept by Burnham.
Army officer.
Collection material in English.
Keywords: Lincoln, Benjamin, -- 1733-1810.; United States. -- Continental Army -- Order-books.; Army officers